INTENSITAS KUNJUNGAN WISATA RELIGI MENJADI PENENTU PENDAPATAN STREET VENDORS KAWASAN MASJID AGUNG BANTEN LAMA - Nurfadhila, Annisa; Suganda, Asep Dadan (I-Economics, 2021)
This research aims to determine the influence of religious tourism visits on the income of street vendors in the Great Mosque of ​​Banten Lama at Serang City, Banten Province, Indonesia. This research used quantitative method, on 79 respondents with simple linear regression analysis. Based on the data and analytical tests, it can be concluded that there is a significant influence of religious tourism visits on the income of street vendors in the Great Mosque of Banten Lama area with a value of sig. 0.000 < 0.05 and the regression coefficient value is positive at 0.633. The magnitude of the influence of religious tourism visits on the income of street vendors (PKL) is 15.4%, while the other 84.6% is influenced by other factors outside this study. This is obtained based on the results of primary data processing using SPSS version 25.0, and it can also be obtained that the coefficient of determination R square (R2) is 0.154 or 15.4%.